Effect of early weaning on subsequent reproduction and calf production by replacement heifers - W.D. Busby; M. McKee; L.R. Corah (Kansas Agricultural Experiment Station Research Reports, 1980)
Analysis of breeding records for 128 percentage Simmental females either weaned early (average age 63 days) or conventionally (average age 194 days) showed no statistically significant difference between early-weaned and nursed heifer calves for subsequent conception rate, calving date, ease of calving, calf birth weight, or 205-day adjusted calf weaning weight.
Keywords: Cattlemen' s Day; 1980; Report of progress (Kansas State University. Agricultural Experiment Station); 377; Beef; Reproduction; Early weaning; Calf production; Replacement heifers